1965
DOI: 10.1103/physrev.138.a1490
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Interference Structure in the Scattered Radiation from Barium Stearate Multilayer Films

Abstract: Recently it was found that x-ray interference phenomena could be observed in the nonspecularly scattered radiation from thin metallic films. In the present investigation, the interference phenomena which manifested themselves in both the specularly and the nonspecularly scattered x rays from multilayer barium stearate films were examined. Several new features were observed in the scattered radiation, and analysis of the interference patterns yielded values of the total multilayer film thickness and the double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1966
1966
2008
2008

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 14 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…6 regardless of the incident angles, from which the distance between the center of the particle to the interface of film/substrate can be calculated (see x4.5). Based on the above discussion, we refer to the fringes as the Kiessig fringes (Kiessig, 1931) at off-specular condition (Kapp & Wainfan, 1965). It is interesting to note that the period of the intensity modulation as a function of i , caused by jB i j cosð þ vÞ, is the same as that of i .…”
Section: The Kiessig Fringesmentioning
confidence: 99%
“…6 regardless of the incident angles, from which the distance between the center of the particle to the interface of film/substrate can be calculated (see x4.5). Based on the above discussion, we refer to the fringes as the Kiessig fringes (Kiessig, 1931) at off-specular condition (Kapp & Wainfan, 1965). It is interesting to note that the period of the intensity modulation as a function of i , caused by jB i j cosð þ vÞ, is the same as that of i .…”
Section: The Kiessig Fringesmentioning
confidence: 99%
“…These well ordered systems have been mostly developed for their potential applications in molecular engineering and have also been used to develop new experimental techniques: see, for example, [143] for references. Early x-ray diffraction experiments [144] revealed the generic bilayer structure of LB films which was further investigated through numerous reflectivity experiments. GIXD can be used to probe the in-plane molecular order, and diffuse off-specular scattering is a unique tool to evidence layer fluctuations and the propagation of defects from the bottom to the top layers.…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%
“…Since the volume in which there are deviations in the refractive index from average is greater for the grain boundary one is led to conclude that the grain boundary makes the largest contribution to the non-specularly scattered radiation. Kapp & Wainfan (1965) have investigated the nonspecular small-angle scattering of X-rays from barium stearate multi-layer films. They found that the intensity of the maxima in the non-specularly scattered radiation decreased much less rapidly with increasing scattering angle than did the intensity maxima in the non-specularly scattered radiation observed in the present investigation.…”
Section: Discussion and Summarymentioning
confidence: 99%